KONFRONTASI DAKWAH ULAMA DAN PEMERINTAH (STUDI KASUS PERSEKUSI ULAMA MASA AMANGKURAT I) - Inayatullah, Ihsanul Haq; Hidayat, Tatang; Istianah, Istianah (LPPM STAI Al-Azhary Cianjur, 2024)
The purpose of this study is to analyze one of the da'wah confrontations that have occurred in Indonesia, namely the case of persecution of ulama during the Amangkurat I period. This research uses a historical approach method with library research. During the time Amangkurat I led Java, there was political turmoil in the Islamic Mataram Sultanate. Amangkurat accused the ulama of collaborating with Pangeran Alit in an attempt to seize the Mataram throne. Which eventually led to the massacre of the ulama and their families by Amangkurat I. Islamic Mataram went into decline during Amangkurat I's time. Many of Amangkurat's policies were detrimental to the people. As a result, there were rebellions that caused Amangkurat I to lose his power.